Answer:
∠EFG = 48°
Step-by-step explanation:
As FH bisects ∠EFG , ∠EFH = ∠HFG .
We know that ∠EFH = (-5x + 89)° . So ∠HFG = ∠EFH = (-5x + 89)°
Also, ∠HFG + ∠EFH = ∠EFG
=> 2(-5x + 89)° = (61 - x)°
=> -10x + 178 = 61 - x
=> 10x - x = 178 - 61
=> 9x = 117
=> x = 117 / 9 = 13
Putting the value of 'x' in ∠EFG gives :-
(61 - x)° = (61 - 13)° = 48°
Solve.
Answer:
591
Step-by-step explanation:
added the 2 in the equation and minused 2000 from that
Answer:
5x^2 - 11x = 1
This is now in standard form, where a = 5, b = -11, and c = 1.
Step-by-step explanation:
To rewrite the equation 11x - 5x^2 + 7 = 6 in standard form, we need to rearrange the terms so that the polynomial is in descending order of degree, with no missing terms. The standard form of a quadratic equation is ax^2 + bx + c = 0, where a, b, and c are constants.
So, let's start by moving the constant term to the right-hand side of the equation:
11x - 5x^2 = 6 - 7
11x - 5x^2 = -1
Next, we can multiply both sides of the equation by -1 to make the coefficient of the x^2 term positive:
5x^2 - 11x = 1
This is now in standard form, where a = 5, b = -11, and c = 1.
Answer:
m∡2 = 64°
Step-by-step explanation:
By definition of vertical angles, the angles opposite of each other are equal each other.
∴ IF ∡1 and ∡2 are vertical angles, AND m∡1 = 64°, THEN m∡2 = 64°. (CPCTC - Definition of Vertical Angles).
~
Vertical angles are equal. Therefore, if ∡1 is 64°, then ∡2 is also 64°.
In mathematics, vertical angles are a pair of non-adjacent angles formed when two lines intersect. By definition, vertical angles are equal in measure.
Therefore, when angle 1 (∡1 ) and angle 2 ( ∡2 ) are vertical angles, if the measure of angle 1 ( m∡1 ) equals 64° as per the question, then the measure of angle 2 (m∡2) will also equal 64°.
So, m∡2 = 64°.
https://brainly.ph/question/287711
#SPJ3